Messianic Jewish Theology: A Preliminary Topology - Richard Harvey (Norsk Tidsskrift for Misjonsvitenskap, 2019)
This article proposes an eight-fold typology of Messianic Jewish theologies. It reviews previous studies and makes proposals for the development of Messianic Jewish Theology. It characterises the views of reflective practitioners within the movement of Messianic Judaism by summarising their views on God, Torah and Israel in the light of the Jewish and Christian theologies that have influenced their development.